Comparing failure mechanisms of ultra-thin continuously reinforced concrete pavements (UTCRCP) under cyclic and monotonic loading - Jacobsz, Schalk Willem (University of Pretoria, 2018)
Dissertation (MEng)--University of Pretoria, 2018.